2011
DOI: 10.3141/2248-06
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Road Safety by Influencing Drivers’ Speed Choice with Sound and Vibration

Abstract: This paper discusses road safety issues and the necessity for safety enhancements, especially on rural roads. Points of discontinuity in infrastructure consistently lead to serious accidents. The major causes of these accidents are inattentiveness and excessive speed. A possible measure to increase attention and reduce speed is installation of transversal rumble strips (TRS). The German government funded a research project to evaluate the use of these strips in the approaches to hazardous bends. The design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Therefore, the increase in sound level was sufficient to alert drivers that they were approaching the intersection. The average rise in acceleration rate (0.68 m/s 2 ) was less than the 2.5 m/s 2 to 4.25 m/s 2 change in previous studies (2,19). The average thickness of 0.16 in.…”
Section: Sound and Vibration Effectscontrasting
confidence: 54%
See 2 more Smart Citations
“…Therefore, the increase in sound level was sufficient to alert drivers that they were approaching the intersection. The average rise in acceleration rate (0.68 m/s 2 ) was less than the 2.5 m/s 2 to 4.25 m/s 2 change in previous studies (2,19). The average thickness of 0.16 in.…”
Section: Sound and Vibration Effectscontrasting
confidence: 54%
“…Tests by Walton and Meyer revealed that an average increase in sound from transverse rumble strips was 10 dB for cars and 4 dB for dump trucks (16). A study by Lank and Steinauer found the A-weighted volume in the area of the transverse rumble strips is on average 10 dB(A) above the basic noise level without transverse rumble strips (2). Horowitz and Nothbohm also measured the sound and vibration level generated by permanent cut-in-pavement (CIP) rumble strips and adhesive rumble strips (17).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One study concluded that the effectiveness of haptic signals depended on the suddenness of vertical deflection. 8 With increased familiarity and awareness of TRS location, the suddenness and thus effectiveness are reduced. In addition, exposure to TRS has been found to cause erratic maneuvers (e.g.…”
Section: Noise and Vibration For Inattentive Driversmentioning
confidence: 99%
“…24 Nonetheless, any depth greater than 0.6 in was not effective in operations. 8 The current study developed a prototype of DRTRS with appropriate dimensions to cause both sufficient in-vehicle noise and vibration to regain the attention of the drivers and be mostly congruent with jurisdictional practice as well. The design and dimensions of DRTRS are discussed in detail in the ''DRTRS design methodology'' section.…”
Section: Design and Dimension Of Trsmentioning
confidence: 99%